Switch in Therapy from Methylphenidate to Atomoxetine in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder: An Analysis of Patient Records - Warrer, Pernille (J Child Adolesc Psychopharmacol, 2016)
Objective: The purpose of this study was to investigate therapy switching from methylphenidate (MPH) to atomoxetine (ATX) in a clinical sample of Danish children and adolescents with attention-deficit/hyperactivity disorder (ADHD); specifically, to determine the duration of MPH treatment before switching to ATX, and the reasons leading to a switch in therapy. Methods: We included 55 patients with ADHD who switched from first-line MPH to second-line ATX during January 01, 2012 and May 15, 2014. Patient and treatment characteristics along with clinical reasons for switching therapy were extracted from individual patients' records. Results: Mean duration of MPH treatment until switch to ATX was 11.2 months (range = 0.3–28.5 months); 36% of the patients switched within the first 6 months, 56% within the first year, and 76% within 1.5 years of initiating MPH; 24% continued MPH treatment for up to 2.5 years prior to switching. Most common reasons for switching were “adverse events” (AEs) (78%), “wish for more optimal day coverage” (24%), and “lack of efficacy” (16%). Other reasons for switching included “patient/parental request” (13%) and “noncompliance” (2%). Most common AEs leading to switch were psychiatric disorders (insomnia, aggression, tic, depression, anxiety) and decreased appetite. Conclusions: Our findings highlight the importance of continuous evaluation of the need for prescription switch to ATX in children and adolescents treated with MPH, taking into consideration various factors including potential AEs, non-optimal day coverage, lack of efficacy, patient/parental preferences, and noncompliance. These factors should be considered, not only at the initial stage of MPH treatment but throughout the whole treatment course.